Pengaruh Partisi Antar Layer Butiran Terhadap Gas CO₂ Pada Batuan Slag Nikel - Amanda Setiawan; Dan Mugisidi (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2025)
The absorption of CO₂ gas by solid materials is an important approach in the development of Carbon Capture and Storage (CCS) technology. Nickel slag, as a solid waste product of nickel smelting, has the potential to be used as a carbon absorbent material as well as a construction material. This study analyzes the effect of inter-particle layer partitions in nickel slag on CO₂ absorption and its implications for slag utilization. The method used is a literature review of journal articles and proceedings discussing the physicochemical properties of nickel slag, types of partitions, diffusion pathways, and carbonation performance. The results of the study show that the presence of solid-solid, solid-liquid, pore/crack, and chemical partitions expands the specific surface area, provides active reaction sites, and forms effective diffusion pathways, thereby increasing the capacity and rate of CO₂ absorption. Engineering the morphology of partitions through mechanochemical activation or chemical treatment is an important strategy for optimizing the function of nickel slag in supporting the application of CCS and the circular economy of industry.